2005
DOI: 10.1167/iovs.04-1347
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Increase of Intraocular Pressure Does Not Alter the Response of Retinal and Optic Nerve Head Blood Flow to Flicker Stimulation

Abstract: A short-term increase in IOP does not alter the response of retinal vessel diameters and ONH blood flow to diffuse luminance flicker, which indicates that increased IOP does not alter retinal or ONH regulation during neuronal stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…This concept does, however, not apply to the ONH, because we have shown previously that, even below the lower level of autoregulation, the vasodilator response to flicker-stimulation is maintained fully. 28 Our results again indicated that ONHBF regulation during OPP modulation is complex and shows wide interindividual variability (Figs. 6, 13).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This concept does, however, not apply to the ONH, because we have shown previously that, even below the lower level of autoregulation, the vasodilator response to flicker-stimulation is maintained fully. 28 Our results again indicated that ONHBF regulation during OPP modulation is complex and shows wide interindividual variability (Figs. 6, 13).…”
Section: Discussionsupporting
confidence: 70%
“…22 By contrast only few studies have investigated optic nerve head blood flow (ONHBF) during changes in OPP. [23][24][25][26][27][28] The aim of our study was to extend our understanding of ONHBF regulation during changes in OPP. Accordingly, we studied blood flow in the optic nerve head (ONH) during an increase in OPP as induced by isometric exercise, as well as during a decrease in OPP as induced by an artificial increase in intraocular pressure (IOP).…”
Section: Discussionmentioning
confidence: 99%
“…Studies supporting the autoregulatory capacity have been performed in healthy humans, nonhuman primates, cats, and rabbits. [17][18][19][20][21][22][23][24][25] The mechanisms that mediate this autoregulatory response in the ONH are unclear. Nitric oxide (NO) is a potent vasodilator that is involved in the maintenance of basal vascular tone, in tonic blood pressure regulation, and in the distribution of blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have been performed to assess vessel diameter changes during stimulation with diffuse luminance flicker in healthy subjects under normal conditions 9,11 or during oxygen breathing, 15 as well as in patients with diabetes, 16,17 glaucoma, 18,19 or systemic hypertension. 19,20 However, the interpretation of the latter experiments is limited by the fact that only data about retinal vessel diameter, but not about volumetric blood flow, are available.…”
mentioning
confidence: 99%